Cylindrical Zwitterionic Particles via Interpolyelectrolyte Complexation on Molecular Polymer Brushes - Pelras, Théophile; Nonappa; Mahon, Clare S.; Müllner, Markus (Macromolecular Rapid Communications, 2021)
The fabrication of macromolecular architectures with high aspect ratio and well‐defined internal and external morphologies remains a challenge. The combination of template chemistry and self‐assembly concepts to construct peculiar polymer architectures via a bottom‐up approach is an emerging approach. In this study, a cylindrical template—namely a core–shell molecular polymer brush—and linear diblock copolymers (DBCP) associate to produce high aspect ratio polymer particles via interpolyelectrolyte complexation. Induced, morphological changes are studied using cryogenic transmission electron and atomic force microscopy, while the complexation is further followed by isothermal titration calorimetry and ξ‐potential measurements. Depending on the nature of the complexing DBCP, distinct morphological differences can be achieved. While polymers with a non‐ionic block lead to internal compartmentalization, polymers featuring zwitterionic domains lead to a wrapping of the brush template.
EPrint Processing Status: Full text deposited in DRO